Evaluation of Nasopharyngeal Swab Collection Techniques for Nucleic Acid Recovery and Participant Experience: Recommendations for COVID-19 Diagnostics - Kinloch, Natalie N (Open Forum Infect Dis, 2020)
Nasopharyngeal swabs are critical to the diagnosis of respiratory infections including coronavirus disease 2019, but collection techniques vary. We compared 2 recommended nasopharyngeal swab collection techniques in adult volunteers and found that swab rotation following nasopharyngeal contact did not recover additional nucleic acid (as measured by human DNA/RNA copy number). Rotation was also less tolerable for participants. Notably, both discomfort and nucleic acid recovery were significantly higher in Asian participants, consistent with nasal anatomy differences. Our results suggest that it is unnecessary to rotate the swab in place following contact with the nasopharynx and reveal that procedural discomfort levels can differ by ethnicity.